2018
DOI: 10.1186/s12885-018-4006-5
|View full text |Cite
|
Sign up to set email alerts
|

An elevated expression of serum exosomal microRNA-191, − 21, −451a of pancreatic neoplasm is considered to be efficient diagnostic marker

Abstract: BackgroundPancreatic cancer is associated with an extremely poor prognosis, so new biomarkers that can detect the initial stages are urgently needed. The significance of serum microRNA (miR) levels in pancreatic neoplasm such as pancreatic cancer and intraductal papillary mucinous neoplasm (IPMN) diagnosis remains unclear. We herein evaluated the usefulness of miRs enclosed in serum exosomes (ExmiRs) as diagnostic markers.MethodsThe ExmiRs from patients with pancreatic cancer (n = 32) or IPMN (n = 29), and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
147
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(151 citation statements)
references
References 29 publications
(33 reference statements)
3
147
1
Order By: Relevance
“…The level of circulating exosomal miR-10b and miR-30c was significantly elevated in 29 PDAC patients relative to chronic pancreatitis patients; however, the level of CA 19-9 was normal or slightly increased in 8 cases [68]. Goto T's study showed that circulating exosomal miR-191, miR-21, and miR451a levels were superior to circulating miRNA levels for differentiating PDAC patients from intraductal papillary mucinous neoplasm (IPMN) patients [69]. Above all, it appears that circulating exosomal miRNA has a potential advantage over circulating miRNAs in PDAC diagnosis, whereas more work is required to compare its diagnostic value to that of tumor tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The level of circulating exosomal miR-10b and miR-30c was significantly elevated in 29 PDAC patients relative to chronic pancreatitis patients; however, the level of CA 19-9 was normal or slightly increased in 8 cases [68]. Goto T's study showed that circulating exosomal miR-191, miR-21, and miR451a levels were superior to circulating miRNA levels for differentiating PDAC patients from intraductal papillary mucinous neoplasm (IPMN) patients [69]. Above all, it appears that circulating exosomal miRNA has a potential advantage over circulating miRNAs in PDAC diagnosis, whereas more work is required to compare its diagnostic value to that of tumor tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Using the PDAC tissues, we examined the relationship between miR‐451a levels and CAB39 mRNA levels and demonstrated a significant inverse correlation. It has been reported that overexpression of miR‐21 downregulates the PDCD4, PTEN and TPM1 genes, promoting cancer progression . Using the PDAC tissues, we examined the association between miR‐21 levels and PDCD4 mRNA levels and showed a significant inverse correlation between them.…”
Section: Discussionmentioning
confidence: 91%
“…Huang et al first reported the use of deep sequencing to discover and characterize profiles of serum‐derived exosomal RNAs . Next generation sequencing was applied to discover serum exosomal RNAs in order to detect biomarkers of diseases . However, some challenges must be considered with regard to serum exosome research, including the difficulty of library construction from low concentration miRNAs, and of serum exosome miRNAs data normalization.…”
Section: Discussionmentioning
confidence: 99%